Quality of life and associated factors among patients with glaucoma attending at Boru Meda General Hospital, Northeast Ethiopia - Hamdu Mohammed; Abebe Tarekegn Kassaw; Fatuma Seid; Samuel Anteneh Ayele (Scientific Reports)
Abstract Glaucoma significantly impacts the well-being of millions of people worldwide and contributes to a decline in quality of life. Therefore, this study aimed to evaluate quality of life and identify influencing factors among glaucoma patients receiving care at Boru Meda General Hospital in Northeast Ethiopia in 2022. A hospital-based cross-sectional study was conducted at Boru Meda General Hospital from July 10 to September 10, 2022. A total of 432 glaucoma patients were selected through a simple random sampling technique. The participants were interviewed via a structured questionnaire, including the modified Glaucoma Quality of Life-15 tool. The data collected were processed by cleaning, coding, and entering into EPi-data version 4.6 and then analysed via SPSS version 26. Variables with a p value less than 0.05 at the 95% confidence interval were considered statistically significant. A total of 417 participants participated in the study, resulting in a response rate of 96.4%. Among them, 187 individuals, accounting for 44.2% (95% CI 39.8–49.9%), reported having poor quality of life. Factors such as being diagnosed for more than 6 years, residing in rural areas, having other ocular diseases, having bilateral glaucoma, receiving treatment for 1–5 years, experiencing moderate anxiety, and facing moderate depression were significantly associated with poor quality of life, with adjusted odds ratios ranging from 2.555 to 8.035. Approximately half of the participants experienced a diminished quality of life, and significant associations were found with rural residence, time since diagnosis, treatment duration, the presence of other ocular conditions, bilateral glaucoma, and levels of anxiety and depression. The implementation of community-based glaucoma screening initiatives aimed at early identification and treatment, particularly those focused on rural communities and individuals with bilateral glaucoma, is crucial.